History of the earth - Creative Educational Society (Mankato, Minn.) (New Delhi : Eurasia, 1971)
Traces briefly the history of the Earth from its birth in the universe through various stages of life on its surface to the development of man.
Includes Index.
Keywords: Historical geology -- Juvenile literature; Geology; Earth (Planet)